CoQ Regulates Brown Adipose Tissue Respiration and Uncoupling Protein 1 Expression - Ching-Fang Chang; Amanda L. Gunawan; Irene Liparulo; Peter-James H. Zushin; Ambre M. Bertholet; Yuriy Kirichok; Andreas Stahl (MDPI AG, 2022)
Coenzyme Q (CoQ, aka ubiquinone) is a key component of the mitochondrial electron transport chain (ETC) and membrane-incorporated antioxidant. CoQ10 deficiencies encompass a heterogeneous spectrum of clinical phenotypes and can be caused by hereditary mutations in the biosynthesis pathway or result from pharmacological interventions such as HMG-CoA Reductase inhibitors, and statins, which are widely used to treat hypercholesterolemia and prevent cardiovascular disease. How CoQ deficiency affects individual tissues and cell types, particularly mitochondrial-rich ones such as brown adipose tissue (BAT), has remained poorly understood. Here we show that pharmacological and genetic models of BAT CoQ deficiency show altered respiration that can only in part be explained by classical roles of CoQ in the respiration chain. Instead, we found that CoQ strongly impacts brown and beige adipocyte respiration via the regulation of uncoupling protein 1 (UCP1) expression. CoQ deficiency in BAT robustly decreases UCP1 protein levels and uncoupled respiration unexpectedly, resulting in increased inner mitochondrial membrane potential and decreased ADP/ATP ratios. Suppressed UCP1 expression was also observed in a BAT-specific in vivo model of CoQ deficiency and resulted in enhanced cold sensitivity. These findings demonstrate an as yet unappreciated role of CoQ in the transcriptional regulation of key thermogenic genes and functions.